ANALYSIS OF THE INTERNAL CONTROL SYSTEM TRADE RECEIVABLES IN PT. INDONESIA ASAHAN ALUMINUM (PERSERO) - Amalia, Riska (Proceeding International Seminar of Islamic Studies, 2024)
This research is a research conducted to determine the application of the internal control system of receivables implemented by PT Indonesia Asahan Alumnunium (Persero). The purpose of this study is to determine whether the internal control system of accounts receivable at PT. Indonesia Asahan Aluminum (Persero) has been running effectively. This study uses a qualitative approach with primary data sources obtained from distributing questionnaires to respondents in companies and secondary data sources in the form of financial reports. The analysis carried out in this study includes descriptive analysis techniques based on internal control system instruments, namely control environment, risk determination, control activities, information and communication as well as supervision and monitoring using the effectiveness level formula. Based on the results of the study, it was concluded that the receivables internal control system at PT. Inalum (Persero) based on the control environment component has been running very effectively while the components of risk assessment, control activities, information communication, and monitoring activities have been running effectively.